Optical Singularity Built on Tiny Holes. Issue 12 (29th October 2021) - Zhou, Changda; Mou, Zhen; Lu, Peiyao; Teng, Shuyun
Abstract: Singular optics is a branch of modern optics, and it usually refers to various singularities including phase, polarization, and energy flux singularities. Lots of excellent researches in foundation and application fields relate to optical singularities. Nanotechnology enables the manipulation of optical singularities in nanometer scale. Metasurfaces consisting of nanoscatterers have aroused intensive interest in recent years because of the ultrathin structure and the powerful light manipulation ability. Optical singular fields generated by metasurfaces built on tiny holes attract much attention. The recent research progress about the optical singular fields in nanoscale is provided here and the physical mechanism of the formation of optical singularities including phase singularity, polarization singularity, and hybrid singularity are discovered in terms of tiny holes. The beneficial reference is provided here to investigate the related works, and the applications of optical singularities in nanometer scale are promoted. Abstract : Custom fields with singularities have extensive applications. This review summarizes singular fields formed by the transmission metasurfaces. Optical vortices, vector fields and hybrid vector fields generated through the amplitude, phase and polarization modulation of tiny holes are provided. This review demonstrates the powerful light manipulation abilities of metasurfaces and promotes the applications of singular fields formed by metasurfaces.